Pendidikan Islam Inklusif - Rizka Ayu Safitri; Kurnia Neta Diyana; Mohammad Rofiq; Silvia Mafâ€ula Zain (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Pluralism is not only a theological awareness, but also a social awareness. This has implications for the awareness that humans live in a plural society in terms of religion, culture, ethnicity and various other diversity. Islamic education, both formal and non-formal, according to Nurcholish Madjid, is a bridge to internalize pluralistic values or inclusive beliefs to students. The Koran is the main foundation of Islamic educational practice. On that basis, Islamic education is required to present social morality so that the humanistic messages contained in the holy book can be used as a guide for social life in a civilized manner. This study uses the literature review method, so that the writing refers to written sources, such as articles, journals, books that are in accordance with the discussion of this research. The results of this research show the framework of thinking about religious pluralism in Islamic education. Â Pluralisme bukan hanya kesadaran yang bersifat teologis, tetapi juga kesadaran yang bersifat sosial. Hal itu berimplikasi pada kesadaran bahwa manusia hidup di tengah masyarakat yang plural dari segi agama, budaya, etnis dan berbagai keragaman lainya. Pendidikan Islam baik formal maupun non formal, menurut Nurcholish Madjid merupakan jembatan penghubung untuk menginternalisasi nilai-nilai pluralistik atau akidah inklusif kepada peserta didik. Al-Quran merupakan landasan utamapraktik pendidikan Islam. Atas dasar itu, pendidikan Islam dituntut menghadirkan moralitas sosial agar pesan humanistik yang termuat di dalam kitab suci bisa dijadikan pedoman hidup bersosial secara beradab. Penelitian ini menggunakan metode kajian pustaka, sehingga penulisannya merujuk pada sumber tulisan, seperti artikel, jurnal, buku yang sesuai dengan pembahasan riset ini. Hasil riset ini menunjukkan tentang kerangka berfikir pluralisme agama dalam pendidikan Islam.